2021
DOI: 10.1371/journal.pone.0261211
|View full text |Cite
|
Sign up to set email alerts
|

Disposal habits and microbial load of solid medical waste in sub-district healthcare facilities and households in Yilo-Krobo municipality, Ghana

Abstract: The study aimed to assess disposal practices and quantify the microbial load present in SMW from ten sub-district level healthcare facilities and 385 households in Yilo Krobo municipality, Ghana. Disposal of solid medical waste (SMW) was assessed by questionnaire-based surveys, unstructured interviews and field observations. Microbiological analysis identified species and counts of bacteria present in SMW from both sources. Sociodemographic factors influencing the method of SMW disposal in households were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The majority of the microorganisms detected in this study are soil-dwelling species that collaborate to develop symbiotic relationships in the soil (O'Callaghan et al, 2022).They make up a significant amount of the nutrients in the soil, which are constantly transferred into the plant growth cycles by the system (Leghariet al,2016). The report of Egbenyah et al (2021), which identified Bacillus cereus, Bacillus subtilis, Escherichia coli, Staphylococcus aureus, Staphylococcus epidermis and Pseudomonas aeruginosa from dump-sites'soils, is consistent with all of the bacteria reported in this study. Also a study by Bassey et al (2021) identified bacterial taxa belonging to genera such as Bacillus, Pseudomonas,Enterobacter, and Clostridium as predominant in dump-site soils and this agrees with bacteria identified in this study.Bacillus subtilis had the highest prevalence of occurrence in this study and is a common soil bacterium known for its ubiquity and ability to thrive in various environments, including dump-sites.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of the microorganisms detected in this study are soil-dwelling species that collaborate to develop symbiotic relationships in the soil (O'Callaghan et al, 2022).They make up a significant amount of the nutrients in the soil, which are constantly transferred into the plant growth cycles by the system (Leghariet al,2016). The report of Egbenyah et al (2021), which identified Bacillus cereus, Bacillus subtilis, Escherichia coli, Staphylococcus aureus, Staphylococcus epidermis and Pseudomonas aeruginosa from dump-sites'soils, is consistent with all of the bacteria reported in this study. Also a study by Bassey et al (2021) identified bacterial taxa belonging to genera such as Bacillus, Pseudomonas,Enterobacter, and Clostridium as predominant in dump-site soils and this agrees with bacteria identified in this study.Bacillus subtilis had the highest prevalence of occurrence in this study and is a common soil bacterium known for its ubiquity and ability to thrive in various environments, including dump-sites.…”
Section: Discussionsupporting
confidence: 89%
“…While the former microbiological assessments of HCW using culture-dependent methods provided limited information, the use of high-throughput next-generation (NGS) sequencing sheds light on the identification of known and unknown microbial communities present in HCW with pinpoint precision ( Egbenyah et al, 2021 ; Joshi et al, 2020 ). In this explorative study, we aimed to characterize the complete microbial communities using high-throughput NGS on Oxford Nanopore Technology (ONT) platform and assess the presence of antibiotic compounds in the microwave pre-treated HCW collected from three different waste operators in Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in Ghana reported a microbial load ranging from 0.036 x 10 3 CFU/mg to 0.167 x 10 3 CFU/mg in hospital waste. Moreover, several pathogenic organisms including Escherichia coli were all isolated from the waste (Egbenyah et al, 2021). This high microbial load might be a result of the different types of waste from different sources that come into contact with the waste.…”
Section: Discussionmentioning
confidence: 99%